2019
DOI: 10.1158/1535-7163.mct-18-1376
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of the Anti-LAG-3 Antibody REGN3767: Characterization and Activity in Combination with the Anti-PD-1 Antibody Cemiplimab in Human PD-1xLAG-3–Knockin Mice

Abstract: In the tumor microenvironment, multiple inhibitory checkpoint receptors can suppress T-cell function, thereby enabling tumor immune evasion. Blockade of one of these checkpoint receptors, PD-1, with therapeutic antibodies has produced positive clinical responses in various cancers; however, the efficacy of this approach can be further improved. Simultaneously targeting multiple inhibitory checkpoint receptors has emerged as a promising therapeutic strategy. Here, we report the development and characterization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
2
42
0
2
Order By: Relevance
“…Since its discovery, many preclinical studies confirmed that the blockade of LAG-3 could support anti-cancer immune responses, leading to a significant delay in tumor growth compared to control conditions [ 3 , 4 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. Notwithstanding these preclinical data, more recent clinical research shows that the blockade of LAG-3 alone might not be an ideal treatment strategy.…”
Section: Clinical Evaluation Of Lag-3 Targeted Treatment In Cancermentioning
confidence: 99%
“…Since its discovery, many preclinical studies confirmed that the blockade of LAG-3 could support anti-cancer immune responses, leading to a significant delay in tumor growth compared to control conditions [ 3 , 4 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. Notwithstanding these preclinical data, more recent clinical research shows that the blockade of LAG-3 alone might not be an ideal treatment strategy.…”
Section: Clinical Evaluation Of Lag-3 Targeted Treatment In Cancermentioning
confidence: 99%
“…In these humanized mice, treatment with cemiplimab and REGN3767 showed increased efficacy in a mouse tumor model and enhanced the secretion of proinflammatory cytokines by tumor-specific T cells. The favorable pharmacokinetics and toxicology of REGN3767 in non-human primates, together with enhancement of antitumor efficacy of anti-PD-1 Ab in preclinical tumor models, supports its clinical development (Burova et al, 2019).…”
Section: Cemiplimab Based Combinational Therapy Preclinical Studymentioning
confidence: 91%
“…Combination treatment with mAbs against both negative receptors significantly reduced tumor growth in mouse models that were unresponsive to monotherapy mAb treatment, which indicates synergy between the PD-1 and LAG-3 inhibitory pathways ( 232 ). Other mouse studies revealed that anti-LAG-3 mAbs enhanced anti-PD-1 therapies and increased the secretion of activating cytokines released by tumor-infiltrating T cells ( 233 ).…”
Section: Nk Cell Irsmentioning
confidence: 99%